APLIKASI DIAGNOSA PENYAKIT SARAF PADA OTAK MENGGUNAKAN METODE MODIFIED K-NEAREST NEIGHBOR BERBASIS ANDROID - Hasan Sajili; Yan Mitha Djaksana (CV. Multi Kreasi Media, 2024)
Disease is a cause of disturbances in the human body and all of these are familiar to humans, because disease is said to be a disorder that is very often experienced by humans. Every human being already knows that their bodies are facing health problems, but most of them, especially those who do not have enough money, do not know about the diseases that are bothering their bodies and how to treat these problems because there is not enough money to see a doctor. One disease that is quite costly is a disease of the brain's nerves, because to treat this disease you have to go straight to the hospital to meet a neurologist to check for the disease. fatal consequences such as acute stroke. The purpose of this research is to build an Android-based neuromuscular diagnosis application by implementing the Modified K-Nearest Neighbor method. The results of this study are successful in implementing the Modified K-Nearest Neighbor method in the Android-based neuromuscular disease diagnosis application.